Suitability of various DNA extraction methods for a traditional Chinese paocai system. Issue 5 (3rd September 2017) - Zhao, Nan; Cai, Jialiang; Zhang, Chuchu; Guo, Zhuang; Lu, Wenwei; Yang, Bo; Tian, Feng-Wei; Liu, Xiao-Ming; Zhang, Hao; Chen, Wei
ABSTRACT: Traditional paocai brine (PB), which is continuously propagated by back-slopping and contains various species of lactic acid bacteria (LAB), is critical for the flavor of paocai. Culture-independent approaches are commonly used to investigate the microbial communities of fermented food. To evaluate the influence of different DNA (DNA) extraction methods on estimates of bacterial community profiles from 4 PBs, the lysis efficiency, DNA yield, purity and denaturing gradient gel electrophoresis (DGGE) profiles of V3 region of a 16S ribosomal ribonucleic acid gene were acquired. The cell lysis pattern of SDS + beads and Lysing matrix E+ beads (methods 3 and 4) showed higher cell lysis efficiency than SDS and SDS + Lysozyme (methods 1 and 2) in all PBs. SDS + beads obtained the largest DNA yield of the 4 methods. Moreover, methods 3 and 4 resulted in higher H′ values and generated more global bacteria profiles than other methods. Overall, our results demonstrate that the properties of PB significantly affect the efficiency of DNA extraction methods. Methods 3 and 4 were both suitable for DNA extraction from PB. Method 3 is more economic, simple and rapid than method 4 for large-scale studies of the bacterial profiles of PB.